2011
DOI: 10.29302/oeconomica.2011.13.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing The Companies‘ Profitability

Abstract: The information about company performance, especially about its profitability, is useful in substantiating managerial decisions regarding potential changes in the economic resources that the company will be able to control in the future. This objective aims achieving superior economic results that will increase the company's competitiveness and will satisfy the shareholders' interests. The paper presents some company performance analysis models, which highlight the influencing factors. The models are based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
42
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 5 publications
12
42
1
13
Order By: Relevance
“…In other words, the use of financial leverage possibly exerts positive influence on the corporate performance. This is consistent with what have been reported by Burja (2011), Seelanatha (2011, Nirajini and Priya (2013), Sivathaasan et al (2013), Ghayas and Akhter (2018). However, the use of financial leverage can also bring firms more financial risks.…”
Section: Financial Leverage and Firm Performancesupporting
confidence: 93%
“…In other words, the use of financial leverage possibly exerts positive influence on the corporate performance. This is consistent with what have been reported by Burja (2011), Seelanatha (2011, Nirajini and Priya (2013), Sivathaasan et al (2013), Ghayas and Akhter (2018). However, the use of financial leverage can also bring firms more financial risks.…”
Section: Financial Leverage and Firm Performancesupporting
confidence: 93%
“…This view has also been confirmed by Kester (1986), Titman and Wessels (1988), Rajan and Zingales (1995), Samarakoon (1999), Booth, Aivazian, Demirgusc-Kunt, and Maksimovic (2001), and Al-Jafari and Samman (2015). On the contrary, Ifeduni and Charlse (2018) found higher profitability because of higher gearing (debt).Expense to revenue ratio has significant negative impact on profitability found by Burja (2011).…”
Section: Review Of Literaturementioning
confidence: 96%
“…The higher expense to revenue ratio of the firm indicates lower profitability. Expense to revenue ratio has negative impact on profitability partially supporting (Burja, 2011). Leverage in this study is calculated by dividing total liabilities to the total assets of the firm.…”
Section: 919mentioning
confidence: 99%
“…Some researchers such as Asimakopoulos et al (2009) and Al-Jafari and Samman (2015) found that leverage is negatively correlated to financial performance; the reason is that high debt requires more resources to pay the debt. However, others like Burja (2011), Humera et al (2011 argue that additional debt can be implemented in a good investment, which will increase financial performance.…”
Section: Leveragementioning
confidence: 99%